Aerobic capacity mediates susceptibility for the transition from steatosis to steatohepatitis. (27th June 2017) - Morris, E. Matthew; McCoin, Colin S.; Allen, Julie A.; Gastecki, Michelle L.; Koch, Lauren G.; Britton, Steven L.; Fletcher, Justin A.; Fu, Xiarong; Ding, Wen‐Xing; Burgess, Shawn C.; Rector, R. Scott; Thyfault, John P.
Abstract : Key points: Low intrinsic aerobic capacity is associated with increased all‐cause and liver‐related mortality in humans. Low intrinsic aerobic capacity in the low capacity runner (LCR) rat increases susceptibility to acute and chronic high‐fat/high‐sucrose diet‐induced steatosis, without observed increases in liver inflammation. Addition of excess cholesterol to a high‐fat/high‐sucrose diet produced greater steatosis in LCR and high capacity runner (HCR) rats. However, the LCR rat demonstrated greater susceptibility to increased liver inflammatory and apoptotic markers compared to the HCR rat. The progressive non‐alcoholic fatty liver disease observed in the LCR rats following western diet feeding was associated with further declines in liver fatty acid oxidation and mitochondrial respiratory capacity compared to HCR rats. Abstract: Low aerobic capacity increases risk for non‐alcoholic fatty liver disease and liver‐related disease mortality, but mechanisms mediating these effects remain unknown. We recently reported that rats bred for low aerobic capacity (low capacity runner; LCR) displayed susceptibility to high fat diet‐induced steatosis in association with reduced hepatic mitochondrial fatty acid oxidation (FAO) and respiratory capacity compared to high aerobic capacity (high capacity runner; HCR) rats. Here we tested the impact of aerobic capacity on susceptibility for progressive liver disease following a 16‐week 'western diet' (WD) high in fat (45% kcal), cholesterol (1% w/w) and sucrose (15% kcal). Unlike previously with a diet high in fat and sucrose alone, the inclusion of cholesterol in the WD induced hepatomegaly and steatosis in both HCR and LCR rats, while producing greater cholesterol ester accumulation in LCR compared to HCR rats. Importantly, WD‐fed low‐fitness LCR rats displayed greater inflammatory cell infiltration, serum alanine transaminase, expression of hepatic inflammatory markers (F4/80, MCP‐1, TLR4, TLR2 and IL‐1β) and effector caspase (caspase 3 and 7) activation compared to HCR rats. Further, LCR rats had greater WD‐induced decreases in complete FAO and mitochondrial respiratory capacity. Intrinsic aerobic capacity had no impact on WD‐induced hepatic steatosis; however, rats bred for low aerobic capacity developed greater hepatic inflammation, which was associated with reduced hepatic mitochondrial FAO and respiratory capacity and increased accumulation of cholesterol esters. These results confirm epidemiological reports that aerobic capacity impacts progression of liver disease and suggest that these effects are mediated through alterations in hepatic mitochondrial function. Key points: Low intrinsic aerobic capacity is associated with increased all‐cause and liver‐related mortality in humans. Low intrinsic aerobic capacity in the low capacity runner (LCR) rat increases susceptibility to acute and chronic high‐fat/high‐sucrose diet‐induced steatosis, without observed increases in liver inflammation. Addition of excess cholesterol to a high‐fat/high‐sucrose diet produced greater steatosis in LCR and high capacity runner (HCR) rats. However, the LCR rat demonstrated greater susceptibility to increased liver inflammatory and apoptotic markers compared to the HCR rat. The progressive non‐alcoholic fatty liver disease observed in the LCR rats following western diet feeding was associated with further declines in liver fatty acid oxidation and mitochondrial respiratory capacity compared to HCR rats.